After Wedding Agreement: Potret Perempuan, Perjodohan, dan Pernikahan - Normuliati, Sri (Muadalah, 2022)
This study aims to describe the portrait of women, matchmaking and marriage in the novel After Wedding Agreement by Mia Chuz. This research uses qualitative research with descriptive method. The data collected in the form of words, phrases, sentences, dialogues of the characters and paragraphs related to the portrait of women on matchmaking and marriage. After the data is collected, the data will be analyzed using descriptive methods. In the analysis process, the research data obtained will be described in detail. After the data analysis process, the last activity is to provide conclusions on the research results. From the research that has been done, obtained data about the portrait of women in responding to matchmaking and marriage, including, (1) a wife who feels insecure about her husband's past, (2) A wife who has a forgiving nature towards her husband's mistakes in the household, (3 ) An independent woman, who has a business that was pioneered even before she got married, (4) A wife who is good at being grateful, trusting, and resigned to her destiny. In addition, the portrait of matchmaking and marriage depicted in Mia Chuz's novel After Wedding Agreement is a marriage based on Islam as it always reminds us of kindness and stays away from prejudice. Penelitian ini bertujuan untuk menggambarkan potret perempuan, perjodohan dan pernikahan dalam novel After Wedding Agreement karya Mia Chuz. Penelitian ini menggunakan penelitian kualitatif dengan metode deskriptif. Data-data yang dikumpulkan berupa kata-kata, frasa, kalimat, dialog para tokoh dan paragraf yang berhubungan dengan potret perempuan terhadap perjodohan dan pernikahan. Setelah data terkumpul, data akan dianalisis dengan menggunakan metode deskriptif. Pada proses analisis, data penelitian yang didapatkan akan dideskripsikan secara detail. Setelah proses analisis data, kegiatan terakhir adalah memberikan kesimpulan terhadap hasil penelitian. Dari Penelitian yang telah dilakukan, diperolehlah data tentang potret perempuan dalam menyikapi perjodohan dan pernikahan, diantaranya, (1) seorang istri yang merasa insecure terhadap masa lalu suaminya, (2) Seorang istri yang mempunyai sifat pemaaf terhadap kesalahan suami dalam rumah tangga, (3) Seorang perempuan yang mandiri, yang mempunyai usaha yang dirintis bahkan sebelum dia menikah, (4) Seorang istri yang pandai bersyukur, tawakal, dan pasrah akan takdir hidupnya. Selain itu, potret perjodohan dan pernikahan yang digambarkan dalam novel After Wedding Agreement karya Mia Chuz adalah pernikahan yang berlandaskan agama Islam seperti selalu mengingatkan dalam kebaikan dan menjauhkan diri dari prasangka.